2021
DOI: 10.1590/1806-9061-2021-1443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Essential Oil and Organic Acid on Performance, Gut Health, Bacterial Count and Serological Parameters in Broiler

Abstract: A total of 1500 day old broiler chicks were grouped into five treatments; each treatment group further consisted of six replicates. Group A was given a control diet having antibiotics. Group B and C were offered essential oil blend at the proportion of 0.1 g/kg and organic acid at the dose rate of 1g/kg. Group D was given both essential oil 0.1 g/kg and organic acid 1g/kg in combination. Group E was offered only a basal diet without antibiotics and considered as a negative control. The trial lasted for 35 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…In summary, the results between various studies were quite different and inconsistent due to the range of inclusion levels, active ingredient compounds, EO types used, basal feed composition, diseases, environmental conditions and herb origin. It was also stated by Iqbal et al (2021).…”
Section: Reviewmentioning
confidence: 71%
See 1 more Smart Citation
“…In summary, the results between various studies were quite different and inconsistent due to the range of inclusion levels, active ingredient compounds, EO types used, basal feed composition, diseases, environmental conditions and herb origin. It was also stated by Iqbal et al (2021).…”
Section: Reviewmentioning
confidence: 71%
“…Czech Journal of Animal Science, 68, 2023 (4): 141-160 https://doi.org/10.17221/99/2022-CJAS ply OAs and OEs has been widely practiced (Iqbal et al 2021;Vinolya et al 2021) and brings remarkable effects. EOs are volatile oils extracted from various plants that have antibacterial, antiviral, and antifungal activities; as well as immunomodulatory, hypolipidaemic and digestive stimulating effects which could be applied to alleviate heat stress in poultry production (Gopi et al 2014;Micciche et al 2018).…”
Section: Reviewmentioning
confidence: 99%
“…This situation is in agreement with a previous study reporting that the inclusion of 1% jujube in the basal diet positively influenced both the live weight and daily live weight of quails during a feeding trial of 38 days [ 45 ]. A supplementation of 0.1 g/kg of essential oils was found to improve the growth performance of broiler chicks through a trial that lasted for 35 days [ 46 ]. Similar findings have been observed in other species.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the relatively stable fluctuations in the citric acid of amaranth sprouts under threshold salinity may represent a crucial aspect of their adaptive mechanism to cope with these conditions. Several studies have reported that the organic acids participate in energy production by entering metabolic pathways and being converted into intermediates, such as acetyl-CoA, which is used in the citric acid cycle (also known as the Krebs cycle) to generate ATP, the body's primary energy source [53].…”
Section: Cnps Enhanced Primary Metabolites Accumulation In Amaranth S...mentioning
confidence: 99%